Promoción de la formación docente en la transformación de aprendizajes (2019)
The purpose of this study was to characterize the conceptions and practices of the focused teachers, of two educational institutions of Piedecuesta, from the Located Work Sessions, which are oriented from the “Todos a aprender” (Let us all learn) Program (PTA), in three axes: Planning, formative evaluation and use of educational materials. To this end, a qualitative design of an interpretive ethnographic type was chosen, which theoretically was supported by authors such as (Reyes, Salcedo, & Perafán, 1999), who make reflections on the conceptions of science and its relation to the practices of teaching and learning, emphasizing teaching as technical, critical and practical or emancipatory action and its results, in relation to learning. The conclusions show that teachers reflect on the need to organize classroom actions in a structured way, which will help show the learning goals. They state that the PTA strategies allow strengthening educational dynamics, conceive formative evaluation as a step to improve learning processes, consider the relevance of educational materials in relation to pedagogical knowledge and the strengths that will be acquired when developing it, understand that good practices guarantee real changes that seek to achieve quality goals. Based on these findings of teachers ‘expectations and suggestions, it was possible to design a pedagogical strategy for curricular strengthening to build the class plan in a fun and innovative way, consolidating the educational processes and responding to the students’ learning needs.